2019
DOI: 10.3389/fonc.2019.01189
|View full text |Cite
|
Sign up to set email alerts
|

MUS81 Participates in the Progression of Serous Ovarian Cancer Associated With Dysfunctional DNA Repair System

Abstract: Objective: Methyl methanesulfonate ultraviolet sensitive gene clone 81 (MUS81) is a structure-specific endonuclease that plays a pivotal role in the DNA repair system of cancer cells. In this study, we aim to elucidate the potential association between the dysfunction of MUS81 and the progression of Serous Ovarian Cancer (SOC).Methods: To investigate the association between MUS81 and prognosis of SOC, immunohistochemistry technology and qPCR were used to analyze the level of MUS81 expression, and transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The crossover junction endonuclease MUS81 interacts with EME1 and EME2 to form a DNA structure-specific endonuclease with substrate preference for branched DNA structures with a 5'-end at the branch nick (44). In addition, MUS81 protein abundance increases in cells following exposure to agents that block DNA replication (45,46).…”
Section: Vpa-caused Hu Sensitization Is Associated With Endonuclease Mus81mentioning
confidence: 99%
“…The crossover junction endonuclease MUS81 interacts with EME1 and EME2 to form a DNA structure-specific endonuclease with substrate preference for branched DNA structures with a 5'-end at the branch nick (44). In addition, MUS81 protein abundance increases in cells following exposure to agents that block DNA replication (45,46).…”
Section: Vpa-caused Hu Sensitization Is Associated With Endonuclease Mus81mentioning
confidence: 99%
“…In a study by Pennington et al (28) compared to germline BRCA1/2 mutations, somatic BRCA1/2 mutations had a similar positive impact on overall survival (OS) and platinum responsiveness. On the other hand, in recent reports, homologous recombination deficiency has gained in importance, in addition to the BRCA mutations, on the targeted treatment (23,29), chemotherapy (30,31), and prognosis (32,33) in EOC patients.…”
Section: Introductionmentioning
confidence: 99%
“…It acts as a DNA replication pressure sensor, regulating the DNA replication forks reactivation, further affecting important DNA damage repair pathways, such as cell non-homologous end joining and homologous recombination repair (HR) ( 6 , 7 ). Inhibition of MUS81 expression in ovarian cancer, significantly impairs cell HR activity ( 8 , 9 ). Our previous research showed that MUS81 was overexpressed in gastric cancer cells and might promote gastric cancer cell invasion and metastasis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%